IMPLEMENTATION OF INTERNATIONAL ELECTORAL STANDARDS ON VOTER REGISTRATION IN ELECTORAL LEGISLATION: COMPARATIVE LEGAL ANALYSIS (American Journal of Research in Humanities and Social Sciences, 2023)
This article examines the role and significance of international electoral standards for voter registration. The constitutional and legal guarantees of the voters of the Republic of Uzbekistan, the implementation of international electoral standards in the national electoral legislation of developed democratic states are analyzed on a legal basis. The author, on the basis of fundamental human and civil rights and freedoms, formulated the most important principles of electoral law. The basic elements of democracy, human rights and fundamental freedoms, as well as the principles of free and fair elections are revealed. The author pays special attention to the definition of such concepts as "formation of the voter list", "state system of registration (registration) of voters", "universal suffrage", "ensuring the rule of law".